Process stabilization by peak current regulation in reactive high-power impulse magnetron sputtering of hafnium nitride - Shimizu, Tetsuhide (Animo Repository, 2016)
A simple and cost effective approach to stabilize the sputtering process in the transition zone during reactive high-power impulse magnetron sputtering (HiPIMS) is proposed. The method is based on real-time monitoring and control of the discharge current waveforms. To stabilize the process conditions at a given set point, a feedback control system was implemented that automatically regulates the pulse frequency, and thereby the average sputtering power, to maintain a constant maximum discharge current. In the present study, the variation of the pulse current waveforms over a wide range of reactive gas flows and pulse frequencies during a reactive HiPIMS process of Hf-N in an Ar–N2 atmosphere illustrates that the discharge current waveform is a an excellent indicator of the process conditions. Activating the reactive HiPIMS peak current regulation, stable process conditions were maintained when varying the N2 flow from 2.1 to 3.5 sccm by an automatic adjustment of the pulse frequency from 600 Hz to 1150 Hz and consequently an increase of the average power from 110 to 270 W. Hf–N films deposited using peak current regulation exhibited a stable stoichiometry, a nearly constant power-normalized deposition rate, and a polycrystalline cubic phase Hf-N with (1 1 1)-preferred orientation over the entire reactive gas flow range investigated. The physical reasons for the change in the current pulse waveform for different process conditions are discussed in some detail.